Isolasi dan Karakterisasi Bakteri Endofit dari Daun Sirsak Annona Muricata L. dan Aktivitas Antibakterinya terhadap Beberapa Bakteri Patogen - Isra Janatiningrum; Akhmad Endang Zainal Hasan; Eny Ida Riyanti (UIN Syarif Hidayatullah Jakarta, 2022)
Soursop (Annona muricata L.) is a plant with many health benefits. Soursop leaves are widely used as traditional medicine by Indonesian citizen for wound infection healing. The antibacterial activity of soursop leaves cannot be separated from the presence of endophytic microbes that live inside. Endophytic bacteria live in plant tissues and have beneficial for their host plants. Endophytic microbes are able to produce same secondary metabolites as their host such as producing antibacterial compounds. Thirty one bacterial endophytes were isolated from soursop leaves that from 3 different regions: Garut, Cianjur, and Sukabumi. Morphologically, endophytic bacterial isolates from the three regions had different diversity. Bacterial isolates were tested for their activity against 4 test pathogenic bacteria, such as Pseudomonas aeroginosa, Escherichia coli, Staphylococcus mutans, and Streptococcus aureus. Antibacterial test using disc diffusion method with chloramphenicol 500 m/mL as positive control. Based on the antibacterial activity test, isolate G42 was able to inhibit all types of test bacteria. G42 isolates forms a zone of inhibition up to 17 mm in P. aeroginosa. Based on 16S rRNA, G42 isolates had similarity with Pantoea wallisii up to 93.24%. This study shows that endophytic bacteria isolated from soursop leaves have the potential to be developed into antibacterial agents.